An improved radiosynthesis of O‐(2‐[18F]fluoroethyl)‐O‐(p‐nitrophenyl)methylphosphonate: A first‐in‐class cholinesterase PET tracer. (15th May 2017) - Neumann, Kiel D.; Thompson, Charles M.; Blecha, Joseph E.; Gerdes, John M.; VanBrocklin, Henry F.
Abstract : O‐(2‐Fluoroethyl)‐O‐( p ‐nitrophenyl) methylphosphonate1 is an organophosphate cholinesterase inhibitor that creates a phosphonyl‐serine covalent adduct at the enzyme active site blocking cholinesterase activity in vivo . The corresponding radiolabeled O‐(2‐[ 18 F]fluoroethyl)‐O‐(p‐nitrophenyl) methylphosphonate, [ 18 F]1, has been previously prepared and found to be an excellent positron emission tomography imaging tracer for assessment of cholinesterases in live brain, peripheral tissues, and blood. However, the previously reported[ 18 F]1 tracer synthesis was slow even with microwave acceleration, required high‐performance liquid chromatography separation of the tracer from impurities, and gave less optimal radiochemical yields. In this paper, we report a new synthetic approach to circumvent these shortcomings that is reliant on the facile reactivity of bis‐(O, O‐p‐nitrophenyl) methylphosphonate, 2, with 2‐fluoroethanol in the presence of DBU. The cold synthesis was successfully translated to provide a more robust radiosynthesis. Using this new strategy, the desired tracer, [ 18 F]1, was obtained in a non‐decay–corrected radiochemical yield of 8 ± 2% (n = 7) in >99% radiochemical and >95% chemical purity with a specific activity of 3174 ± 345 Ci/mmol (EOS). This new facile radiosynthesis routinely affords highly pure quantities of[ 18 F]1, which will further enable tracer development of OP cholinesterase inhibitors and their evaluation in vivo . Abstract : O‐(2‐[ 18 F]fluoroethyl)‐O‐(p‐nitrophenyl) methylphosphonate, [ 18 F]1, has been prepared with the purpose of assessing cholinesterases in live brain, peripheral tissues, and blood using a new optimized radiosynthetic strategy. The desired tracer, [ 18 F]1 was obtained in a nondecay corrected radiochemical yield of 8 ± 2% (n = 7) in >99% radiochemical and >95% chemical purity with a specific activity of 3174 ± 345 Ci/mmol (EOS). This new facile radiosynthesis will further enable tracer development of OP cholinesterase inhibitors and their evaluation in vivo .